HAZOP : guide to best practice : guidelines to best practice for the process and chemical industries - Crawley, Frank; Tyler, Brian (Elsevier, 2015)
HAZOP: Guide to Best Practice, 3rd Edition describes and illustrates the HAZOP study method, highlighting a variety of proven uses and approaches. This updated edition brings additional experience with which to assist the reader in delivering optimum safety and efficiency of performance of the HAZOP team. HAZOP is the most widely-used technique in the process industries for the identification of hazards and the planning of safety measures. This book explains how to implement HAZOP techniques in new facilities and apply it to existing facilities. The content covers many of the possible applications of HAZOP and takes you through all the stages of a study. This simple, easily digestible book is a favorite in the chemical and process industries.